Concrete radiation shielding nuclear physics, concrete properties, design and construction - Kaplan, M. F. (Essex Longman Scientific & Technical, 1989)
Experience has shown that concrete is an effective, versatile and economical material for the construction of radiation shielding and this book has been designed to give the engineer a complete understanding of design and production methods using this material. This book outlines the procedures for the design of concrete radiation shields, the special problems associated with their construction and cost, the effects of elevated temperatures and radiation on concrete and its physical, mechanical and nuclear properties. Reviewing the widely scattered information and data available on this subject, this book tries not only be of use to civil engineers concerned with the design and construction of concrete shielding, but also to nuclear engineers, students and anyone involved in research in this field.
Includes bibliographies and index.
Keywords: Nuclear reactors -- Shielding (Radiation); Concrete construction